EAPH-13. PHASE I STUDY OF INTRAVENTRICULAR INFUSIONS OF AUTOLOGOUS EX VIVO EXPANDED NK CELLS IN CHILDREN WITH RECURRENT/REFRACTORY MALIGNANT POSTERIOR FOSSA TUMORS OF THE CENTRAL NERVOUS SYSTEM. Issue 2 (22nd June 2018) - Khatua, Soumen; Gopalakrishnan, Vidya; Sandberg, David; Ketonen, Leena; Johnson, Jason; Cooper, Laurence; Moyes, Judy; Lee, Dean; Meador, Heather; Rytting, Michael; Liu, Diane; Zaky, Wafik
Abstract: Prognosis of recurrent/refractory medulloblastoma, ependymoma and atypical teratoid/rhabdoid neoplasms (AT/RT) remains dismal. Preclinical data showing efficacy of activated/propagated NK cells to lyse and kill these tumor cells in culture and in mice have been demonstrated, along with feasibility and safety of infusions of biologic agents into the ventricles. The ongoing phase I trial evaluates for the first time in humans, safety of infusions of autologous NK cells directly into the ventricles of patients with these tumors. Assessment of antitumor activity, and correlative biologic studies are being evaluated to define the immunophenotype and function of expanded NK cells. Patients receive three cycles of NK-cell infusions over 12 weeks through an Ommaya reservoir. To date, 9 patients have been enrolled, 8 patients achieved successful expansion of their NK cells, and 7 patients received up to 27 infusions each of NK cells at doses up to 3x10e7/m2/infusion. Currently this study is enrolling patients in the last cohort. This phase I study has so far demonstrated safety with no dose-limiting toxicity attributable to the infused NK cells. Significant CSF pleocytosis is seen in patients receiving NK cells with the increased dosage, with no evidence of infection. Influx of CD4 + and CD8 + T cells into the CSF in noted. This could suggest a proinflammatory environment induced by higher doses of NK cell infusion. This study also intends to evaluate the migration and persistence of NK cells with novel neuroimaging techniques to correlate efficacy outcome and the pharmacokinetics of NK cells.